The Microvascular Response to Transdermal Iontophoresis of Insulin is Mediated by Nitric Oxide. (November 2013) - Iredahl, Fredrik; Tesselaar, Erik; Sarker, Saikat; Farnebo, Simon; Sjöberg, Folke
Abstract: Objective: Insulin has direct effects on blood flow in various tissues, most likely due to endothelial NO production. We investigated whether insulin delivered to the skin by iontophoresis increases microvascular perfusion and whether this effect is partly or completely mediated by the release of NO. Methods: In healthy subjects, regular insulin and monomeric insulin were delivered to the skin by cathodal iontophoresis. The skin was pretreated either with L‐NAME or control solution (PBS) using anodal iontophoresis. Microvascular responses were measured using laser Doppler flowmetry. Results: A dose‐dependent increase in perfusion was observed during iontophoresis of regular and monomeric insulin. The maximum perfusion was significantly elevated compared with control after PBS (regular insulin 53.6 (12.7–95.6) PU vs. 4.2 (3.4–4.8) PU, p = 0.002; monomeric insulin 32.6 (8.9–92.6) PU vs. 5.9 (3.4–56.0) PU, p = 0.03). The microvascular response to insulin was abolished after L‐NAME (regular insulin: 25.6 (11.6–54.4) PU vs. control: 4.7 (2.9–11.5) PU, p = 0.15; monomeric insulin 10.9 (5.4–56.8) PU vs. control: 4.7 (2.9–11.5) PU, p = 0.22). Conclusions: The main finding is that iontophoresis of insulin induces a dose‐dependent vasodilation in the skin, which could be suppressed after pretreatment with a NO synthase inhibitor. This suggests that vasodilation in the skin after iontophoresis of insulin is mediated by the NO pathway.